Pengaruh Kualitas Pelayanan dan Promosi Terhadap Kepuasan Pengunjung Event Launching Honda CR-V Hybrid Pada CV Muda Art Project Medan - Siregar, Puteri Ardhia; Siregar, Indra (Abdimas Indonesian Journal, 2024)
This study aims to understand the effect of service quality and promotion on visitor satisfaction at the Honda CR-V Hybrid launch event held by CV Muda Art Project in Medan, both partially and simultaneously. This research uses an associative approach. The population in this study were all visitors to the event, totalling 1.200 people, with a sample of 100 people. Data were collected using interviews, observations, and questionnaires. Data analysis was carried out using Multiple Linear Regression Test, Hypothesis Test (t test and F test), and Coefficient of Determination. The partial test results show that service quality has a tcount value of 5.139 which is greater than the t table (1.985) with a significance level of 0.001 (<0.05), which means that there is a positive and significant effect of service quality on customer satisfaction. For the promotion variable, the tcount value is 2.270, which is greater than the t table (1.985), with a significance of 0.025 (<0.05), which indicates a positive and significant effect of promotion on customer satisfaction. Simultaneously, service quality and promotion have a significant positive effect on visitor satisfaction, with an Fcount value of 45.702 which is greater than Ftable (3.328) and a significance of 0.000 (<0.05). Thus, it can be concluded that service quality and promotion together have a positive and significant effect on visitor satisfaction at the Honda CR-V Hybrid launch event in Medan.